Cover Picture: Transfer Hydrogenation of Ethyl Levulinate to γ‐Valerolactone Catalyzed by Iron Complexes (Chin. J. Chem. 4/2015). Issue 4 (April 2015) - Dai, Nan; Shang, Rui; Fu, Mingchen; Fu, Yao
<x xml:space="preserve">Abstract</x> The cover picture shows a new and green transformation path for the synthesis of γ‐valerolactone from biomass‐derived ethyl levulinate, which is realized by iron‐catalyzed transfer hydrogenation. γ‐Valerolactone is a valuable chemical, which can be used as liquid fuel, food additive, solvent and also intermediate for organic synthesis. By utilizing Casey's catalyst and cheap isopropanol as hydrogen source, γ‐valerolactone can be generated in 95% yield. Addition of catalytic amount of base is important to achieve good yield. More details are discussed in the communication by Fu et al. on page 405–408.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>